Shades of Sovereignty: Understanding Sovereignty in International Politics - Shah, Apekshya (Journal of International Affairs, 2018)
Correction: On 29th June 2020, the author’s name was changed from Apkeshya Shah TO Apekshya Shah. This paper analyses the concept of Westphalian sovereignty and its practices among states, particularly in the bilateral relationship between Nepal and India. The notion of Westphalian sovereignty, basically a principle of non-intervention in the internal matters of other states, has been a contested concept since the beginning of its inception. Despite numerous international agreements, system-affecting and system-influencing countries have not refrained from meddling into the internal affairs of system-ineffectual states. Taking the issue of alleged Indian interference in Nepal’s internal affairs into consideration, this paper examines levels and degrees of correction in accusations and assertions. And if it is correct then how can we understand it better. The first part of the paper discusses the conceptual frame of state sovereignty and its evolution over time. Then, the issue of the exercise of sovereignty is explored and, concurrently, the compromise of state sovereignty is also explained before analysing Nepal-India relations. Next, the Nepal-India relations are analysed.